2017
DOI: 10.1186/s12879-017-2269-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and HIV co-infection among pregnant women in Rwanda

Abstract: BackgroundHepatitis C virus (HCV) infection is a pandemic causing disease; more than 185 million people are infected worldwide. An HCV antibody (Ab) prevalence of 6.0% was estimated in Central African countries. The study aimed at providing HCV prevalence estimates among pregnant women in Rwanda.MethodsHCV surveillance through antibody screening test among pregnant women attending antenatal clinics was performed in 30 HIV sentinel surveillance sites in Rwanda.ResultsAmong 12,903 pregnant women tested at antena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
4
18
8
Order By: Relevance
“…This overall prevalence among pregnant women in our setting was relatively higher compared to retrospective findings published by Kopilovic et al [4] in some European countries. On the other hand, our findings for HCV prevalence among pregnant women at our setting is higher than findings reported from Nigeria (1.5%), Malawi (2.0%), United Kingdom (0.8%), Brazil (0.2%) and Central African region (2.0%), however, lower than overall estimated prevalence for sub-Saharan African countries (3.0%) [3]. The explanation for these variations could be due to differences in geographical patterns and varying physician test ordering practices, care-seeking and disclosure behaviors of pregnant women, or factors that are related to HCV risk [10].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…This overall prevalence among pregnant women in our setting was relatively higher compared to retrospective findings published by Kopilovic et al [4] in some European countries. On the other hand, our findings for HCV prevalence among pregnant women at our setting is higher than findings reported from Nigeria (1.5%), Malawi (2.0%), United Kingdom (0.8%), Brazil (0.2%) and Central African region (2.0%), however, lower than overall estimated prevalence for sub-Saharan African countries (3.0%) [3]. The explanation for these variations could be due to differences in geographical patterns and varying physician test ordering practices, care-seeking and disclosure behaviors of pregnant women, or factors that are related to HCV risk [10].…”
Section: Discussioncontrasting
confidence: 93%
“…Following the identification of the hepatitis C virus in 1989 [2], and the development of specific diagnostic assays, hepatitis C infection is now recognized as a worldwide public health problem which affect 1.3 -8.0% of the world's population. Globally, the prevalence of hepatitis C virus (HCV) infection was estimated to be between 1.2 and 3.8% according to World Health Organization (WHO) Global Burden of Disease, with more than 185 million people infected worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of HCV and HIV co‐infection among pregnant women varies across settings. One study in Rwanda reported that 3.9% of pregnant women with HCV were co‐infected with HIV . In a Western/Central European cohort of pregnant women living with HIV, 12% were co‐infected with HCV .…”
Section: Introductionmentioning
confidence: 99%
“…In Rwanda, the prevalence of HCV is not well known among the general population. Recent studies conducted in specific population groups have found the prevalence of anti-HCV (HCVAb), a marker for exposure to HCV, to be between 4.3-4.7% among people living with HIV(PLHIV) and 2.6% among pregnant women 9,10 . Among these studies none have assessed risk factors for HCV in Rwanda.…”
Section: Introductionmentioning
confidence: 99%